Influence of ultrasonic melt treatment on microstructure and mechanical properties of AlSi9Cu3 alloy - Puga, Hélder (2011)
A novel MMM (Multi-frequency, Multimode, Modulated) ultrasonic (US) technology was used to refine the as cast microstructure and improve the mechanical properties of a AlSi9Cu3 alloy. Ultrasonic vibration was isothermally applied to the melt for 120 seconds at different temperatures slightly above the liquidus temperature of the alloy, using different electric power values, before pouring into a metallic mould. The microstructure of the cast samples was characterized by optical and scanning electron microscopy and energy dispersive spectrometry. Ultrasonic vibration promoted the formation of small -Al globular grains, changed the size and morphology of intermetallic compounds and distributed them uniformly throughout the castings. Ultimate Tensile Strength and Strain were increased to 332 MPa and 2.9% respectively, which are 50% and 480% higher than the values obtained for castings produced without vibration. The microstructure morphology and the alloy mechanical properties were found to depend on the electric power and the melt temperature, and by using a suitable combination of these parameters it is possible to achieve high refinement efficiency by treating the melts in the liquid state.